Exchange Rate Dynamics and Volatility of the Nepali Rupee (1998-2020): Forecasts, Financial Risks, and Policy Implications - Shahi, Amrit (Journal of Nepalese Management and Research, 2025)
The research examines Nepali Rupee (NPR) to US Dollar (USD) exchange rate patterns from 1998 to 2020, while creating predictions for 2021-2024 to assess financial risks and inform policymakers. Monthly average data (n = 271) were obtained from the Nepal Rastra Bank’s portal and analyzed using R studio. The study examined volatility measures, including percent and marginal changes, and performed three time-series diagnostic tests. The ETS (M, Ad, N) model was used for short-term predictions, with results showing accuracy for predictions (RMSE = 1.24; MAE = 0.88; MAPE ≈ 1.03%). The analysis reveals that the NPR experiences ongoing long-term depreciation with regular brief market fluctuations. The ETS model provides accurate short-term predictions, but its predictive bands expand when forecasting into the future, indicating increasing market unpredictability. The study also examines the impact of exchange rate fluctuations on import-dependent firms, exporters, and foreign currency projects. The research recommends risk management strategies for businesses, including natural hedging and forward contracts. It also suggests two macroeconomic strategies: reserve management and derivatives market expansion. The study demonstrates that univariate models, like ETS, fail to detect structural changes after 2020, notably due to COVID-19 and worldwide inflation. It recommends using ARIMAX, GARCH, and machine learning models for better forecasting. The study emphasizes the need for additional tests to verify model accuracy through out-of-sample data evaluation.